Information support of the remote nitrogen monitoring system in agricultural crops - Lysenko, Vitalii; Opryshko, Aleksey; Komarchuk, Dmytro; Pasichnyk, Natalia; Zaets, Natalia; Dudnik, Alla (My University, 2018)
The article addresses issues on application of unmanned aerial vehicles (UAV) to monitor nitrogen nutrition through the example of wheat plants. The optical spectral range can be used to monitor exploitation of the UAV. It is recommended to develop specialized spectral indices for such equipment. The article provides calibration curves for nitrogen nutrition monitoring.
Keywords: uav; monitoring; nutrition; fertilizers; drones; моніторинг; насичення; добрива; дрони; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка